Prevention of noise induced hearing loss in worker: A literature review - Setyawan, Febri Endra Budi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Noise induced hearing loss (NIHL) is a hearing loss due to noise that exceeds the hearing threshold limit value (TLV) in a work environment. Impacts of this disorder are decreased concentration, fatigue, headaches, sleep disturbances, and loss of job. Therefore, it is very important for industry stakeholders and workers to understand about the NIHL, so they can prevent and rehabilitate  this problem. Risk factors that affect degrees of severity of deafness are noise intensity, frequency, duration of exposure per day, length of work, individual sensitivity, age and other factors that can cause deafness. Based on this, it can be understood that an amount of received exposure of noise energy will be similarly proportional as obtained damage. In general, NIHL cannot be cured but can be prevented and rehabilitated. Its prevention can be by applying hearing conservation program (HCP) such as noise measurement procedure, noise control, periodic audiometry measurement, hearing protection, worker education, recording, and evaluation. Some of benefits that can be obtained from the hearing conservation program are as a guide to diagnose hearing loss to prevent health impacts from noise exposure.